Influence of pH Adjustment Parameter for Sol–Gel Modification on Structural, Microstructure, and Magnetic Properties of Nanocrystalline Strontium Ferrite - Raba’ah Syahidah, Azis; Sakinah, Sulaiman; Idza Riati, Ibrahim; Azmi, Zakaria; Jumiah, Hassan; Nor Nadhirah, Che Muda; Rodziah, Nazlan; Norlaily, M. Saiden; Yap, Wing Fen; Muhammad Syazwan, Mustaffa; Khamirul Amin, Matori (Springer Open, 2018)
Synthesis of nanocrystalline strontium ferrite (SrFe12O19) via sol–gel is sensitive to its modification parameters. Therefore, in this study, an attempt of regulating the pH as a sol–gel modification parameter during preparation of SrFe12O19 nanoparticles sintered at a low sintering temperature of 900 °C has been presented. The relationship of varying pH (pH 0 to 8) on structural, microstructures, and magnetic behaviors of SrFe12O19 nanoparticles were characterized by X-ray diffraction (XRD), field emission scanning microscope (FESEM), and vibrating sample magnetometer (VSM). Varying the pH of precursor exhibited a strong effect on the sintered density, crystal structure and magnetic properties of the SrFe12O19 nanoparticles. As the pH is 0, the SrFe12O19 produced relatively largest density, saturation magnetization, Ms , and coercivity, Hc, at a low sintering temperature of 900 °C. The grain size of SrFe12O19 is obtained in the range of 73.6 to 133.3 nm. The porosity of the sample affected the density and the magnetic properties of the SrFe12O19 ferrite. It is suggested that the low-temperature sintered SrFe12O19 at pH 0 displayed Ms of 44.19 emu/g and Hc of 6403.6 Oe, possessing a significant potential for applying in low-temperature co-fired ceramic permanent magnet.